Penerapan Metode Weighted Product dan Simple Additive Weighting dalam Sistem Penunjang Keputusan Pemilihan Keramik Berkualitas (Studi Kasus : Toko Keramik Abadi) - Achmad Fauzan Syaputra; Yuhandri Yunus; Harkamsyah Andrianof (LPPM Politeknik Jambi, 2023)
Rapid development in the world of information and communication technology as a result of globalization have also had a major impact on certain fields including the industrial sector, on industrial sector, technology is very useful in searching, storing, distributing and presenting information. Indonesia has an increasingly promising ceramics indsutry development from years. Ceramics is a building material that functions to coat the floor surface to make it look more attractive. The presence of various vendors with varied motifs and qualities has created confusion among consumers in choosing ceramics. Implementing a decision support system when choosing product quality is able to provide structured assessments that assist consumers and business stakeholders in evaluating the selection of quality ceramics. The SPK method used in designing this system is the weighted product and simple additive weighting methods. The WP method is able to simplify a complex unstructured problem by using multiplication in connecting attribute ratings, while the SAW method is able to provide a more precise assessment because it is based on the criterion value of predetermined preference weights. The results of the assessment of these two methods are expected to be taken into consideration in the selection of quality ceramics appropriately.